2017
DOI: 10.1002/ldr.2664
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Grazing Alters Soil Trace Gas Fluxes from Grasslands in the Foothills of the Rocky Mountains, Canada

Abstract: Long-term cattle grazing may degrade grassland soils, but how soil CO 2 , CH 4 and N 2 O fluxes respond to long-term cattle grazing is poorly understood. Therefore, we quantified soil CO 2 , CH 4 and N 2 O fluxes in response to four levels (none, light, heavy, very heavy) of long-term (>65 years) cattle grazing on a rough fescue grassland in the foothills of the Rocky Mountains, Canada over three grazing seasons. The grazed grassland soils emitted 37 to 51% more CO 2 than non-grazed soils. Grazed grassland soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
(119 reference statements)
2
14
0
Order By: Relevance
“…At the same time, grazing may facilitate the growth of plants with shallow roots (Ingram et al 2008) and hence increase the surface layer root C and N stocks. With VH treatment, lower litter and standing crop C stocks may be related to the decrease of aboveground primary production (Li et al 2008;Gao et al 2018) and a smaller mass of residual crop following grazing. Livestock dung and urine could increase the soil available N (Frank and Evans 1997) and hence increase plant N content (Mikola et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, grazing may facilitate the growth of plants with shallow roots (Ingram et al 2008) and hence increase the surface layer root C and N stocks. With VH treatment, lower litter and standing crop C stocks may be related to the decrease of aboveground primary production (Li et al 2008;Gao et al 2018) and a smaller mass of residual crop following grazing. Livestock dung and urine could increase the soil available N (Frank and Evans 1997) and hence increase plant N content (Mikola et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hoof action of livestock may influence C and N storage through its effects on litter decomposition rate and soil physical status (Semmartin et al 2008). Soil is the main reservoir of C and N in grassland ecosystems, and previous studies have shown that livestock grazing alters the accumulation and release of soil C and N (Tanentzap and Coomes 2012;Gao et al 2018). However, the direction and magnitude of grazing effects are highly contextdependent and regulated by the complex interactions among grazing strategy, climate, and soil (McSherry and Ritchie 2013).…”
Section: Responsible Editor: Zucong Caimentioning
confidence: 99%
“…Counter-intuitive, no significant differences were found among the three grazing treatments in the top of the slope. Gao et al [47] investigated soil trace gas fluxes from grasslands in the foothills of the Rocky Mountains, Alberta. Grazed grassland soils had 37 to 51% greater CO2 emissions?…”
Section: Soc Nutrient Cycle and Greenhouse Has Emissions As A Functimentioning
confidence: 99%
“…For example, a study, in an alpine steppe on the Tibetan Plateau, China, thought that no grazing enhanced CH 4 uptake by 17.8% and 33.8% in 2009 and 2010, respectively, while its effect on CO 2 emission (ecosystem respiration) was not significant [55]. Gao et al reported that long-term cattle grazing increased soil CO 2 fluxes, while the grazing effect on CH 4 uptake depended on precipitation [56]. The effects of grazing on ecosystem respiration and methane flux are complex.…”
Section: Effects Of Grazing On Ecosystem Respiration and Ch 4 Fluxmentioning
confidence: 99%